Dentoskeletal effects of aesthetic and conventional twin block appliances in the treatment of skeletal class II malocclusion: a randomized controlled trial - Mohamed Najati Alsilq; Mohamed Youssef (Scientific Reports)
Abstract Twin block appliances are commonly used to treat skeletal class II malocclusion. However, many adverse effects, such as lower incisor protrusion and a bulky nature, can be observed. To overcome these effects, a modified twin block was designed, which uses vacuum-formed hard plates (VFPs) instead of acrylic plates. This clinical trial evaluated the skeletal and dentoalveolar changes resulting from a modified twin block (aesthetic twin block) (ATB) in comparison with conventional twin block (CTB) in addition to levels of esthetics and discomfort. A two-arm parallel group randomized clinical trial was performed at the Department of Orthodontics, University of Damascus, Syria. Fifty-two patients (33 females and 19 males) aged 12.23 ± 0.77 years with skeletal class II division 1 malocclusion caused by mandibular retrognathism were included. The participants were randomly assigned to a study group according to a simple randomization method using a numbered and sealed envelope. The experimental group was treated with an aesthetic twin block, and the control group was treated with a conventional twin block. Sixteen angular variables and eleven seventeen linear variables (measured in millimeters) were evaluated before the treatment (T0) and at the end of the active phase of the treatment (T1) on lateral cephalometric radiographs and dental casts to study the skeletal and dentoalveolar changes, and a questionnaire was used to assess the levels of esthetic and discomfort. There was a statistically significant change in the ANB angle between the ATB group (−2.70 ± 0.84) and the CTB group (−1.92 ± 0.81°) (P = 0·002) and between the SNB angle of the ATB group (2.72 ± 1.54°) and the CTB group (1.72 ± 1.41°) (P = 0·02). The Jarabak ratio decreased significantly in the CTB group (−0.65 ± 1.37%) (P = 0.02) and increased significantly in the ATB group (0.84 ± 1.44%) (P = 0.007), with significant differences between the two groups (P = 0.000). The change in upper incisor angulation was statistically significant (−1.88 ± 1.48°) for the ATB group and (−3.5 ± 4.18°) for the CTB group (P = 0·001). The change in lower incisor angulation was 1.34 ± 2.08° for the ATB group and 3.88 ± 2.47° for the CTB group, which was statistically significant (P = 0·000). ATB had more control of vertical growth, lower incisor and upper incisor angulation and was more aesthetically acceptable. Trial registration: (NCT05418413) (14/06/2022).